Financial Health and Operational Risks of Indonesian Energy Corporations:A Post-Pandemic Evaluation - Hanipah Hanipah; Maisarah Nabila; Mayla Nurwahidiah (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to examine and analyze the relationship between financial ratios, company growth, dividend policy, operating costs, and operating income on financial distress. Design/methodology/approach – This study employs quantitative data. The sample consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The hypothesis testing technique used is multiple regression analysis with the assistance of E-Views 9 software. Findings – The results indicate that financial ratios have a positive and statistically significant effect on financial distress. Company growth has a negative but statistically insignificant effect on financial distress. Dividend policy also has a negative and statistically insignificant effect on financial distress. Meanwhile, operating costs and operating income have a positive and statistically significant effect on financial distress. Research limitations/implications – This research is limited to the 2022–2024 observation period and industrial sector companies listed on the Indonesia Stock Exchange (IDX), and only examines receivable turnover, audit committee size, operating capacity, and real interest rate as determinants of corporate financial distress. The practical implication of this research is that the findings may serve as a reference for management and investors in assessing and anticipating corporate financial distress risk. JEL : G33, G32, G35, L25, D24